(untitled) (Lex Scientia Law Review, 2024)
Efficiency in communicating and searching for information makes things easier for us in the current era of modern digitalization. This is directly proportional to the emergence of various forms of digital crime, such as online gender-based violence. The existence of a bias in terms of the meaning of technology by women which is influenced by the history and culture of construction makes it necessary to understand technology as part of a culture that expresses and consolidates relations between men and women. Technology with its sophistication seems to have a masculine nature. The feminine nature inherent in women is considered not in harmony with the way technology works. The focus of the discussion in this writing is to find how the concept of cyberfeminism should be relevant to policy based on digital gender equity in Indonesia. The research method used is doctrinal with a statutory approach, a conceptual approach, and a historical approach. The results of the research show that in terms of normative legal policy in Indonesia, legal regulations have been created to make preventive efforts and overcome the problem of gender-based violence, especially against women. However, the phenomenon of gender-based violence continues to occur, especially in vulnerable groups, namely women and children. Of course, all existing policies must be responsive to digital-based gender equity, especially the Sexual Violence Crime Law and the Information and Electronic Transactions Law.